AMSR2データを用いた北極海の海氷厚推定 - 舘山, 一孝; Tateyama, Kazutaka; 猪上, 淳; Inoue, Jun; 星野, 聖太; Hoshino, Seita; 中野渡, 拓也; Nakanowatari, Takuya; 佐々木, 奨太; Sasaki, Shota; 田中, 康弘; Tanaka, Yasuhiro (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference presentation